Предмет: Математика, автор: VipPhoenixVip

Нужно решение для простого примера :З

Приложения:

Ответы

Автор ответа: dim10102806
0
√(3-2√2)*⁴√(17+12√2)=⁴√((3-2√2)^2(17+12√2))=⁴√((9-12√2+8)(17+12√2))=⁴√((17-12√2)(17+12√2))=⁴√(289-288)=1
Ответ: {1}

VipPhoenixVip: Слишком сложно)
Автор ответа: koingreel
0

 \sqrt{(1 -  \sqrt{2}) {}^{2}  }  \sqrt[4]{(3 + 2 \sqrt{2}) {}^{2}  }  =  \\  \\ ( \sqrt{2}  - 1) \sqrt{3 + 2 \sqrt{2} }  =  \\   \\  ( \sqrt{2}  - 1 \sqrt{(1 +  \sqrt{2} } ) {}^{2}  =  \\  \\ ( \sqrt{2}  - 1) (1 +   \sqrt{2} ) = \\  \\ ( \sqrt{2}  - 1)( \sqrt{2}  + 1) =  \\  \\ 2 - 1 \\  \\  = 1
ОТВЕТ: 5
Похожие вопросы